2011
DOI: 10.1103/physrevlett.106.040505
|View full text |Cite
|
Sign up to set email alerts
|

Robust Quantum State Transfer in Random Unpolarized Spin Chains

Abstract: We propose and analyze a new approach for quantum state transfer between remote spin qubits. Specifically, we demonstrate that coherent quantum coupling between remote qubits can be achieved via certain classes of random, unpolarized (infinite temperature) spin chains. Our method is robust to coupling strength disorder and does not require manipulation or control over individual spins. In principle, it can be used to attain perfect state transfer over arbitrarily long range via purely Hamiltonian evolution and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
285
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(288 citation statements)
references
References 53 publications
1
285
0
2
Order By: Relevance
“…if dipole-dipole interaction is suppressed because of a large spatial separation of the spins [36]. Nevertheless, an interaction can still be possible by using the indirect coupling via neighboring spins, as proposed for nitrogen-vacancy centers [37,38]. With our method we can create entanglement between the end spins of a spin chain, even if the coupling strengths between the spins are only known up to a certain extent.…”
Section: Mediated Interaction With Inhomogeneous Couplingsmentioning
confidence: 99%
“…if dipole-dipole interaction is suppressed because of a large spatial separation of the spins [36]. Nevertheless, an interaction can still be possible by using the indirect coupling via neighboring spins, as proposed for nitrogen-vacancy centers [37,38]. With our method we can create entanglement between the end spins of a spin chain, even if the coupling strengths between the spins are only known up to a certain extent.…”
Section: Mediated Interaction With Inhomogeneous Couplingsmentioning
confidence: 99%
“…Note that for the simplest case of spin chains, the symmetry of the modes ensures the network is already balanced 7,8,37 . However, to drive transport in arbitrary networks, one does need an active control scheme for balancing.…”
Section: Perfect Qst By On-resonance Balancingmentioning
confidence: 99%
“…Engineering the coupling between spins can improve the transport fidelity 4 , even allowing for perfect quantum state transport (QST), but it is difficult to achieve in experimental systems. Remarkable work 5,6 found relaxed coupling engineering requirements -however, even these proposals still required linear chains with nearest-neighbor couplings 7,8 or networks will all equal couplings 9 . These requirements remain too restrictive to allow an experimental implementation, since manufacturing highly regular networks is challenging with current technology [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea was first introduced in [1], where it was shown that the natural dynamics of a Heisenberg ferromagnetic spin chain can achieve high-fidelity transfer of qubits over distances as long as 80 lattice units.In contrast to this traditional "passive" protocol, different approaches soon emerged. One idea was to engineer the couplings between the various spins in the chain in such a way that states are transferred with perfect [2]- [9] or with arbitrary high fidelity [10]- [16]; in addition, some minimal external control on the chain dynamics was also introduced in order to achieve similar results [18]- [26].…”
Section: Introductionmentioning
confidence: 99%